2019
DOI: 10.4187/respcare.06866
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow Nasal Cannula Versus Standard Oxygen Therapy After Extubation in Liver Transplantation: A Matched Controlled Study

Abstract: BACKGROUND: High-flow nasal cannula (HFNC) is a key component of oxygen therapy and has largely been used in patients with acute respiratory failure. We conducted a matched controlled study with the aim to compare the preventive use of oxygen therapy delivered by HFNC versus via air-entrainment mask (standard O 2) after extubation in adult subjects with liver transplantation for reducing postextubation hypoxemia. METHODS: Twenty-nine subjects with liver transplantation who received HFNC after extubation (HFNC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
(50 reference statements)
1
7
0
1
Order By: Relevance
“…The nonsuperiority of HFNC over standard oxygen therapy in postoperative subjects reported by Gaspari et al 1 is in agreement with the results of similar studies, which included subjects who had undergone major abdominal surgery, 2 lung resection, 3 or cardiac surgery (both obese 4 and normal weight) subjects. 5 Based on this and previous studies, can we state that HFNC should not be used in postoperative patients?…”
supporting
confidence: 90%
See 2 more Smart Citations
“…The nonsuperiority of HFNC over standard oxygen therapy in postoperative subjects reported by Gaspari et al 1 is in agreement with the results of similar studies, which included subjects who had undergone major abdominal surgery, 2 lung resection, 3 or cardiac surgery (both obese 4 and normal weight) subjects. 5 Based on this and previous studies, can we state that HFNC should not be used in postoperative patients?…”
supporting
confidence: 90%
“…7 But these effects would not have much, if any, effect on the more common causes of postoperative hypoxemia, such as atelectasis, aspiration, or pneumonia. 8 The equivalence in hypoxemia seen in the study by Gaspari et al, 1 which was not expected, may not be surprising because of the protocols for oxygen delivery. The F IO 2 in both groups of subjects was titrated to maintain an S pO 2 of Ն93%.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Assessment of the use of HFNC compared to conventional oxygen therapy immediately after extubation was the objective of several RCTs. [52][53][54][55][56][57][58][59] Hospital and ICU LOS were not different. Herna ´ndez et al 52 found lower re-intubation within 72 h of extubation using HFNC compared to conventional oxygen therapy in subjects at low risk of extubation failure (P ¼ .004).…”
Section: High-flow Nasal Cannula Versus Standard Oxygenmentioning
confidence: 85%
“…Nach mehreren Metaanalysen [ 19 , 20 , 21 , 22 ] kann High-flow-Sauerstoff
High-flow-Sauerstoff
beim primär hypoxämischem Versagen als Alternative zur NIV eingesetzt werden. Angesichts heterogener Patientengruppen mit unterschiedlichen Risiken für ein Postextubationsversagen zeigen Studiendaten sowie Metaanalysen keinen konsistenten Vorteil der High-flow-Therapie gegenüber der reinen Sauerstoff- oder NIV-Therapie zur Reintubationsvermeidung und insbesondere nicht bezüglich des Outcomes, einschließlich der Intensivmortalität [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Vielmehr zeigt eine aktuelle Arbeit von Thille et al.…”
Section: Stellenwert Der Nichtinvasiven Beatmung Im Einfachen Bzw Schwierigen Weaningunclassified